Fe-Doped ZnO nanoparticle toxicity: assessment by a new generation of nanodescriptors. Issue 46 (19th November 2018) - Burk, Jaanus; Sikk, Lauri; Burk, Peeter; Manshian, Bella B.; Soenen, Stefaan J.; Scott-Fordsmand, Janeck J.; Tamm, Tarmo; Tämm, Kaido
Abstract : Toxicity and cancer-killing potency of Fe-doped ZnO nanoparticles can be reliably modelled using atomistic nanodescriptors. Abstract : In the search for novel tools to combat cancer, nanoparticles (NPs) have attracted a lot of attention. Recently, the controlled release of cancer-cell-killing metal ions from doped NPs has shown promise, but fine tuning of dissolution kinetics is required to ensure specificity and minimize undesirable toxic side-effects. Theoretical tools to help in reaching a proper understanding and finally be able to control the dissolution kinetics by NP design have not been available until now. Here, we present a novel set of true nanodescriptors to analyze the charge distribution, the effect of doping and surface coating of whole metal oxide NP structures. The polarizable model of oxygen atoms enables light to be shed on the charge distribution on the NP surface, allowing the in detail study of the factors influencing the release of metal ions from NPs. The descriptors and their capabilities are demonstrated on a Fe-doped ZnO nanoparticle system, a system with practical outlook and available experimental data.